2016
DOI: 10.1109/tbdata.2016.2564982
|View full text |Cite
|
Sign up to set email alerts
|

Agile Big Data Analytics for Web-Based Systems: An Architecture-Centric Approach

Abstract: This article contributes an architecture-centric methodology, called AABA (Architecture-centric Agile Big data Analytics), to address the technical, organizational, and rapid technology change challenges of both big data system development and agile delivery of big data analytics for Web-based Systems (WBS). As the first of its kind, AABA fills a methodological void by adopting an architecture-centric approach, advancing and integrating software architecture analysis and design, big data modeling and agile pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…Interestingly, we have noted that both source types recognize occurrences of PoC exploits, attacks, and vulnerabilities at the same time. It has been shown that there are time delays, e.g., the Germination Period, both between the identification of vulnerabilities and the production of PoC exploits and also between hostile attacks targeting these vulnerabilities and the corresponding PoC exploits [6] [23]. We intend to broaden these data sources, thus taking a big data approach, to show something more general, by identifying as many contexts as possible and determining whether the time delays are different in different contexts.…”
Section: The Germination Period and Big Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, we have noted that both source types recognize occurrences of PoC exploits, attacks, and vulnerabilities at the same time. It has been shown that there are time delays, e.g., the Germination Period, both between the identification of vulnerabilities and the production of PoC exploits and also between hostile attacks targeting these vulnerabilities and the corresponding PoC exploits [6] [23]. We intend to broaden these data sources, thus taking a big data approach, to show something more general, by identifying as many contexts as possible and determining whether the time delays are different in different contexts.…”
Section: The Germination Period and Big Datamentioning
confidence: 99%
“…Large volumes and different varieties of data will have to be collected from the main data sources, ingested, stored and prepared for analysis. A big data repository is thus planned for storing the raw data to allow "schema on read" [5] [6] for different types of analysis. There are tremendous technical challenges in terms of preparing data for analysis.…”
Section: Collecting and Managing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [15] propose an architecture-centric methodology to address the technical, organizational, and rapid technology change challenges of Big Data system development for Big Data Web analytics using an agile approach. This architecture-centric agile approach was able to cost-effectively achieve business goals and architecture agility in 11 Web-based systems presented by the authors.…”
Section: Software Architecture For Big Datamentioning
confidence: 99%
“…Our prior work [6][7][8][9] have discussed about the existing technqiues pertaining to significance of classification approach, tools of big data analytics, and applicability of big data analytics over healthcare sector. Chen et al [10] have presented architecture for supportability of agile methodologies over big data. Dabek and Caban [11] have introduced a technique where a visualization mechanism is designed for modeling the user interaction.…”
Section: Introductionmentioning
confidence: 99%